Critical care pharmacy workforce: UK deployment and characteristics in 2015. (11th October 2017) - Borthwick, Mark; Barton, Greg; Bourne, Richard S; McKenzie, Catherine
Abstract: Objective: Clinical pharmacists reduce medication errors and optimize the use of medication in critically ill patients, although actual staffing level and deployment of UK pharmacists is unknown. The primary aim was to investigate the UK deployment of the clinical pharmacy workforce in critical care and compare this with published standards. Methods: An electronic data entry tool was created and distributed for UK critical care pharmacy services to record their critical care workforce deployment data. Key findings: Data were received for 279 critical care units in 171 organizations. Clinical pharmacist input was identified for 98.6% of critical care units. The median weekday pharmacist input to critical care was 0.045 whole time equivalents per Level 3 (ICU) bed with significant interregional variation. Weekend services were sparse. Pharmacists spent 24.5% of time on the multidisciplinary team ward round, 58.5% of time on independent patient review and 17% of time on other critical care professional support activities. There is significant variation in staffing levels when services are stratified by highest level of competence of critical care pharmacist within an organization ( P = 0.03), with significant differences in time spent on the multi-disciplinary ward round ( P = 0.010) and on other critical care activities ( P = 0.009), but not on independent patient review. Conclusions: Investment in pharmacy services is required to improve access to clinical pharmacy expertise at weekends, on MDT ward rounds and for other critical care activities.